A Visual Tracking System for Honey Bee (Hymenoptera: Apidae) 3D Flight Trajectory Reconstruction and Analysis. Issue 2 (16th April 2021) - Sun, Cong; Gaydecki, Patrick
Abstract: We describe the development, field testing, and results from an automated 3D insect flight detection and tracking system for honey bees ( Apis mellifera L.) (Hymenoptera: Apidae) that is capable of providing remarkable insights into airborne behavior. It comprises two orthogonally mounted video cameras with an observing volume of over 200 m 3 and an offline analysis software system that outputs 3D space trajectories and inflight statistics of the target honey bees. The imaging devices require no human intervention once set up and are waterproof, providing high resolution and framerate videos. The software module uses several forms of modern image processing techniques with GPU-enabled acceleration to remove both stationary and moving artifact while preserving flight track information. The analysis system has thus far provided information not only on flight statistics (such as speeds and accelerations), but also on subtleties associated with flight behavior by generating heat maps of density and classifying flight patterns according to patrol and foraging behavior. Although the results presented here focus on behavior in the locale of a beehive, the system could be adapted to study a wide range of airborne insect activity.